Determination of the Protonation Constants of Triazole Derivatives in Non-Aqueous Solvents - Islamoglu, Fatih; Kahveci, Bahittin; Ozil, Musa; Akyuz, Emine; Mentese, Emre; Pinar Ekinci, Arife (Asian Journal of Chemistry, 2010)
Different 17 triazole derivatives were titrated with tetrabutylammonium hydroxide in four non-aqueous solvents (isopropyl alcohol, tert-butyl alcohol, N,N-dimethylformamide and acetonitrile), using potentiometric method. The half neutralization potential values and the corresponding pKa values were determined for all cases.